Moral Messages in the Syair “Petuah Perempuan Bima”: an Anthropolinguistic Perspective (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to identify and analyze the moral messages embedded in the Syair Petuah Perempuan Bima and to explore how the poem reflects the relationship between language and culture in Bima society. A descriptive qualitative method was employed, using an anthropolinguistic framework. Data were collected through in-depth interviews, participatory observation, and field notes focused on oral practices in the Bima community, where the tradition of this syair is actively preserved. The findings reveal that the Syair Petuah conveys five main categories of moral values: religious values (faith, worship, and the afterlife), moral values (honesty, patience, humility), social values (tolerance, harmony, cooperation), educational values (encouragement to learn and respect teachers), and cultural values (preservation of customs and local identity). The poem demonstrates that language functions not only as a means of communication but also as a medium for transmitting cultural values and reinforcing the social identity of women in Bima society. This research contributes to the preservation of intangible cultural heritage and enriches the fields of anthropolinguistics and character education based on local wisdom in Indonesia